RESEARCH ON THE EQUIVALENT THEORIES AND TENSION PROPERTIES OF SEMI-REENTRANT HONEYCOMB STRUCTURE (Jixie qiangdu)
The semi-reentrant honeycomb structure has the characteristics of zero Poisson's ratio,and is a hybrid form composed of hexagonal honeycomb structure and reentrant honeycomb structure.Therefore,the deformation characteristics of a semi-reentrant honeycomb cell can be obtained through deformation coupling of a hexagonal honeycomb cell(with a positive angle)and a reentrant honeycomb cell(with a negative angle).Based on the different mechanisms of bending,tensile,hinge,and shear deformation of hexagonal honeycomb cells and reentrant honeycomb cells,and considering the influence of the cell wall thickness,a deformation mechanism of semi-reentrant honeycomb cells was established.An equivalent theory of mechanical properties of in-plane deformation was derived to predict its elastic modulus and Poisson's ratio in different directions in the plane.The effects of geometric parameters(tilt arm length l,vertical arm length h,angle α,angle β,structure thickness d and unit wall thickness t)on in-plane tensile properties(elastic modulus and Poisson's ratio)of semi-reentrant honeycomb structure were analyzed using the finite element method.By comparing the finite element simulation results with the prediction results of the equivalent theory,the effectiveness and accuracy of the equivalent theoretical model were verified.Comparing the prediction results of different equivalent theories shows the importance of considering the effects of different deformation mechanisms and wall thickness to accurately predict in-plane tensile properties.